"Being Mean" and "Spazzing Out:" Social Calibration and Gender in Brazilian Jiu Jitsu Training. Issue 3 (28th February 2022) - Burke, Brigid E. K.
Abstract : This article draws on ethnographic data from a Brazilian Jiu Jitsu gym to describe "social calibration" as ongoing interstitial work through which actors assess expectations of intensity and adjust their behaviors and dispositions accordingly. It explores two intensity breaches at the gym: "spazzing out" and not "being mean" enough. Using a microsociological lens, it analyses gym members' understandings of, and reactions to, these breaches. This study provides theoretical insight into micro‐interactional processes of social calibration used to negotiate and align intensity levels with prevailing norms, and shows how through these processes practitioners transgress or reinforce gendered expectations. A video abstract is available at: https://bit.ly/Burke2022 .